Axial and flexural behaviour of circular reinforced concrete columns strengthened with reactive powder concrete jacket and fibre reinforced polymer wrapping. (30th May 2018) - Hadi, Muhammad N.S.; Algburi, Atheer H.M.; Sheikh, M. Neaz; Carrigan, Allister T.
Highlights: A new strengthening technique for circular RC columns is presented. The technique consists of jacketing RC columns with RPC and wrapping with FRP. Jacketing with RPC increased the yield and ultimate loads of circular RC columns. FRP wrapping of jacketed columns increased the ductility and energy absorption capacity. Abstract: This paper investigates axial and flexural behaviour of circular reinforced concrete (RC) columns strengthened with reactive powder concrete (RPC) jacket and fibre reinforced polymer wrapping. The experimental results of 16 circular RC column specimens have been presented. The specimens were divided into four groups of four specimens. Column specimens of the first group were the reference RC specimens without any strengthening, specimens of the second group were strengthened by wrapping with two layers of carbon fibre reinforced polymer (CFRP), specimens of the third group were jacketed with a 25 mm thick layer of RPC and specimens of the fourth group were jacketed with a 25 mm thick layer of RPC then wrapped with a single layer of CFRP. Test results demonstrated that jacketing with a thin layer of the RPC enhanced significantly the ultimate axial and flexural loads as well as energy absorption of circular RC column specimens. Wrapping the RPC jacketed specimens with CFRP improved the ultimate axial load, ductility and energy absorption of the specimens.